2011
DOI: 10.1016/j.ejvs.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Carotid ‘Vulnerable Plaque’ by Contrast-enhanced Ultrasonography: Correlation with Plaque Histology, Symptoms and Cerebral Computed Tomography

Abstract: CEUS with dB-E is indicative of the extent of plaque neovascularisation. It can be used therefore as a marker for vulnerable plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 31 publications
0
55
0
5
Order By: Relevance
“…CEUS has recently been used to visualize intraplaque neovascularization as an element of vulnerability. 4,[8][9][10][11][12] The source of neovascularization is direct branching from the vasa vasorum or the intimal surface. These areas are very fragile, and plaque hemorrhage can easily occur.…”
Section: Resultsmentioning
confidence: 99%
“…CEUS has recently been used to visualize intraplaque neovascularization as an element of vulnerability. 4,[8][9][10][11][12] The source of neovascularization is direct branching from the vasa vasorum or the intimal surface. These areas are very fragile, and plaque hemorrhage can easily occur.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between atherosclerotic plaque morphology in the carotid artery and cerebrovascular events has been of interest for many years [16,20,33,55,57]. Compositional factors contribute to the vulnerability of an atherosclerotic plaque to rupture, as opposed to degree of stenosis or patient symptoms [12].…”
Section: Introductionmentioning
confidence: 99%
“…Plaque cap thickness has been correlated with plaque vulnerability. In a study of 22 patients, who underwent CEA, a greater number of plaques with cap thickness defined as <200 μm was found to be associated with cerebrovascular events (p=0.01) 57 . In another study, the histological analysis of 105 plaques in asymptomatic and symptomatic patients demonstrated that the presence of an echogenic cap was four times more frequent in the symptomatic ones than in those with asymptomatic plaques (p<0.05) 58 .…”
Section: Surfacementioning
confidence: 99%